Fabric capable of scavenging free radicals and active oxygen, preparation method of fabric and application of fabric in underwear

By using components such as ionic liquids, defatted cotton, chitosan, alginic acid and MOFs ligands in the fabric, the Cu-cMOFs structure is prepared, combined with tetraamic copper sulfate, the problem of increasing skin free radicals and reactive oxygen species in summer is solved, and the problem of increased skin is achieved. Efficient removal and sterilization, and the effect of preventing skin diseases.

CN119318406APending Publication Date: 2025-01-17NANTONG UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411286541.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-13
Publication Date
2025-01-17

AI Technical Summary

Technical Problem

The climate in summer is hot, and the skin is easily affected by factors such as sunlight, insect bites, and sweat accumulation, leading to an increase in free radicals and reactive oxygen species, damaging the skin barrier and increasing the risk of skin diseases. It is difficult for existing fabrics to effectively remove these harmful substances.

Method used

Compound nanocellulose membranes are prepared by components such as ionic liquid, defatted cotton, chitosan, alginic acid and MOFs ligand, and Cu-cMOFs structure is formed through ultrasonic hydrothermal reaction, combining tetraamic copper sulfuric acid to form a highly efficient catalytic function. Fabric, capable of removing free radicals and reactive oxygen species.

Benefits of technology

This fabric not only has strong bactericidal and urea oxidative degradation capabilities, but also forms a gel layer on the skin surface to maintain water activity, significantly improve the scavenging ability of free radicals and reactive oxygen species, and prevent skin diseases and aging.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119318406A_ABST
    Figure CN119318406A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of textiles, and particularly relates to a fabric capable of scavenging free radicals and active oxygen, a preparation method of the fabric and application of the fabric in underwear. The preparation method comprises the following steps: dissolving absorbent cotton, chitosan and alginic acid in an ionic liquid together to prepare a cellulose solution, adding a ligand to prepare a spinning solution, carrying out electrostatic spinning and ethanol coagulation bath to obtain a composite nano cellulose membrane, carrying out ultrasonic treatment with a copper tetraamminesulfate DMF solution, carrying out a hydrothermal reaction, and washing with water to obtain the composite nano cellulose membrane. And drying to obtain the skincare underwear fabric capable of scavenging free radicals and active oxygen. The fabric can resist bacteria, has certain affinity to the skin, is high in water retention capacity, and can remove free radicals and active oxygen on the surface of the skin and prevent skin diseases and skin aging.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of textiles, and in particular to a fabric capable of removing free radicals and active oxygen, a preparation method thereof and application thereof in underwear. Background Art

[0002] In summer, the sun is strong, the weather is hot, the ozone concentration is high, and the humidity is high, which can easily induce a variety of skin diseases or aggravate existing skin diseases. For example, after being bitten by midges, mosquitoes, tussock moths, rove beetles, caterpillars and other insects, papules, wheals, erythema, blisters and the like will appear on the skin. Abuse of skin drugs can easily lead to contact dermatitis, the symptoms of which are erythema, swelling, blisters and the like on the skin at the contact site, and burning, pain and itching. In addition, in summer, due to the strong reaction of the human body to sunlight, it is easy to cause photosensitive skin diseases, which can cause redness and swelling on the back of the hands and face, and blisters and other symptoms in severe cases. Due to the high temperature of the weather, the sweat is not excreted smoothly and accumulates in the skin or on the surface of the skin, which can cause sweat disorder skin diseases such as prickly heat, sweat herpes, sweat gland cysts and the like. Sweat soaking the skin and dust adhesion can easily lead to infection with staphylococci, streptococci and fungi, causing folliculitis, abscesses, tinea corporis, sweat spots and tinea cruris. These surface symptoms will aggravate the metabolic pressure of the skin to varying degrees, causing an increase in free radicals and reactive oxygen on the skin surface, ultimately causing damage and destruction to the skin barrier. Summary of the invention

[0003] In view of this, the purpose of the present invention is to provide a fabric that can remove free radicals and active oxygen, a preparation method thereof and its application in underwear. The fabric is not only antibacterial, has a certain affinity for the skin, has a strong water retention capacity, but also can remove free radicals and active oxygen on the skin surface, and prevent skin diseases and skin aging.

[0004] In order to solve the above technical problems, the technical solutions provided by the present invention are as follows:

[0005] In a first aspect of the present invention, a method for preparing a fabric capable of removing free radicals and active oxygen is provided, comprising the following steps:

[0006] S1. After the ionic liquid and water are mixed, absorbent cotton, chitosan and alginate are added to prepare a cellulose solution;

[0007] S2. Adding MOFs ligands to the cellulose solution obtained in step S1, stirring and mixing thoroughly to obtain a spinning solution;

[0008] S3. electrospinning the spinning solution obtained in step S2 from top to bottom to obtain a composite nanocellulose membrane;

[0009] S4. Immerse the composite nanocellulose membrane obtained in step S3 in a solution of tetraammine copper sulfate in N,N-dimethylformamide, perform hydrothermal reaction after ultrasonication, wash with water, and dry to obtain a fabric that can remove free radicals and active oxygen.

[0010] In some embodiments of the present invention, the cellulose solution is prepared by mixing the ionic liquid and water, adding absorbent cotton, chitosan and alginic acid, heating to 80-90° C., and stirring thoroughly to dissolve to obtain a cellulose solution.

[0011] In some embodiments of the present invention, the ionic liquid is one of 1-allyl-3-methylimidazolium chloride, 1-methyl-3-butylimidazolium chloride and 1-ethyl-3-methylimidazolium chloride.

[0012] In some embodiments of the present invention, the weight average molecular weight of the chitosan is 300,000-500,000, and the degree of deacetylation is 80-95%.

[0013] In some embodiments of the present invention, in step S1, the feed ratio of the absorbent cotton, chitosan, alginate, ionic liquid and water is (5.8-6.5) g: (1.5-2.0) g: (1.5-2.0) g: (75-90) g: (10-20) ml.

[0014] In some embodiments of the present invention, in step S2, the MOFs ligand is one of 1,3,5-benzenetricarboxylic acid, terephthalic acid and 4,4',4",4"'-methanetetrayltetrabenzoic acid.

[0015] In some embodiments of the present invention, in step S2, the content of MOFs ligands in the spinning solution is 3.5-5.0 w / v%.

[0016] In some embodiments of the present invention, in step S3, the lower half of the collecting roller of the electrospinning is immersed in anhydrous ethanol; the voltage of the electrospinning is 18-20 kV, the receiving distance is 15-18 cm, and the injection flow rate is 3-5 ml / h.

[0017] In some embodiments of the present invention, the composite nanocellulose membrane obtained in step S4 has a thickness of 80-100 μm.

[0018] In some embodiments of the present invention, in step S4, the bath ratio of the immersion is 40-50:1, and the concentration of the tetraamminecopper sulfate in the N,N-dimethylformamide solution of tetraamminecopper sulfate is 1.2-3.0 w / v%.

[0019] In some embodiments of the present invention, in step S4, the ultrasonic power is 500-800 W and the time is 20-30 min.

[0020] In some embodiments of the present invention, in step S4, the hydrothermal reaction temperature is 100-110° C., and the reaction time is 60-120 min.

[0021] In a second aspect of the present invention, a fabric capable of removing free radicals and active oxygen prepared according to the above preparation method is also provided.

[0022] In the third aspect of the present invention, there is also provided a use of the above-mentioned fabric capable of scavenging free radicals and active oxygen in underwear.

[0023] Compared with the prior art, the present invention has the following beneficial effects:

[0024] 1) In the technical solution provided by the present invention, chitosan and alginate form coordination bonds with copper ions together with the hydroxyl groups on cellulose, and form a composite organic metal framework structure Cu-cMOFs on the basis of Cu-MOFs ligands, which has efficient catalytic function, can effectively remove free radicals and reactive oxygen, and exhibit highly active SOD-like and CAT-like enzyme activities.

[0025] 2) In the fabric obtained by the preparation method provided by the present invention, after Cu-cMOFs is activated by free radicals and active oxygen, it has outstanding bactericidal performance and urea oxidation degradation ability, which can give the fabric a strong bactericidal function and keep the skin and fabric clean.

[0026] 3) Conventional cellulose has weak water absorption and water retention capabilities. The present invention, by incorporating alginate and chitosan, can maintain a high water activity in slightly acidic, neutral and slightly alkaline environments, and can form a gel layer on the skin surface, which helps Cu-cMOFs capture free radicals and active oxygen. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The scanning electron microscope photograph of the fabric for scavenging free radicals and active oxygen prepared in Example 1 is shown;

[0028] Figure 2 The free radical scavenging test results of the fabrics of Examples 1-3 and Comparative Examples 1-3 and commercially available underwear fabrics are shown;

[0029] Figure 3 The antibacterial test results of the fabrics of Examples 1-3 and Comparative Examples 1-3 and commercially available underwear fabrics are shown;

[0030] Figure 4 The results of the active oxygen scavenging and urea decomposition experiments of the fabrics of Examples 1-3 and Comparative Examples 1-3 and commercially available underwear fabrics are shown. DETAILED DESCRIPTION

[0031] In order to further understand the present invention, preferred embodiments of the present invention are described below in conjunction with examples, but it should be understood that these descriptions are only for further illustrating the features and advantages of the present invention, rather than limiting the claims of the present invention.

[0032] Example 1

[0033] A method for preparing a fabric capable of removing free radicals and active oxygen comprises the following steps:

[0034] 1. Preparation of cellulose solution: 6.2 g of cotton wool, 1.7 g of chitosan with a weight average molecular weight of 400,000 and a deacetylation degree of 85%, and 1.7 g of alginic acid were dissolved in a solution obtained by mixing 80 g of 1-allyl-3-methylimidazolium chloride and 15 ml of water, heated to 85° C., and stirred thoroughly to dissolve to obtain a cellulose solution.

[0035] 2. Preparation of spinning solution: Add 4.0 w / v% of MOFs ligand 1,3,5-benzenetricarboxylic acid to the cellulose solution prepared in step 1, stir and mix thoroughly to obtain a spinning solution.

[0036] 3. Preparation of composite nanocellulose membrane: The spinning solution obtained in step 2 was electrospun from top to bottom with a voltage of 19 kV, a receiving distance of 16 cm, a jet flow rate of 4 ml / h, and the lower half of the collecting roller was immersed in anhydrous ethanol to obtain a composite nanocellulose membrane with a membrane thickness of 90 μm.

[0037] 4. Preparation of fabrics capable of scavenging free radicals and active oxygen: The composite nanocellulose membrane obtained in step 3 was immersed in a 2.0 w / v% tetraammine copper sulfate N,N-dimethylformyl solution at a bath ratio of 45:1, and subjected to hydrothermal reaction at 700 W power ultrasound for 25 min, the reaction temperature was 105 ° C, the reaction time was 100 min, and then washed with water and dried to obtain a fabric capable of scavenging free radicals and active oxygen. Figure 1 This is a scanning electron microscope photo. The diameter of the fiber is 850±26nm and the thickness is evenly distributed.

[0038] Example 2

[0039] A method for preparing a fabric capable of removing free radicals and active oxygen comprises the following steps:

[0040] 1. Preparation of cellulose solution: 6.5 g of cotton wool, 2 g of chitosan with a weight average molecular weight of 500,000 and a deacetylation degree of 95%, and 2 g of alginic acid are dissolved in a solution obtained by mixing 90 g of 1-methyl-3-butylimidazole chloride and 20 ml of water, heated to 90° C., and stirred thoroughly to dissolve to obtain a cellulose solution.

[0041] 2. Preparation of spinning solution: Add 5.0 w / v% of MOFs ligand terephthalic acid to the cellulose solution prepared in step 1, stir and mix thoroughly to obtain a spinning solution.

[0042] 3. Preparation of composite nanocellulose membrane: The spinning solution obtained in step 2 was electrospun from top to bottom with a voltage of 20 kV, a receiving distance of 18 cm, a jet flow rate of 5 ml / h, and the lower half of the collecting roller was immersed in anhydrous ethanol to obtain a composite nanocellulose membrane with a membrane thickness of 100 μm.

[0043] 4. Preparation of fabrics capable of scavenging free radicals and active oxygen: The composite nanocellulose membrane obtained in step 3 was immersed in a 3.0 w / v% tetraammine copper sulfate N,N-dimethylformyl solution at a bath ratio of 50:1, and subjected to hydrothermal reaction at 800 W power ultrasound for 20 min, the reaction temperature was 110°C, the reaction time was 60 min, and then washed with water and dried to obtain a fabric capable of scavenging free radicals and active oxygen.

[0044] Example 3

[0045] A method for preparing a fabric capable of removing free radicals and active oxygen comprises the following steps:

[0046] 1. Preparation of cellulose solution: 5.8 g of cotton wool, 1.5 g of chitosan with a weight average molecular weight of 300,000 and a deacetylation degree of 80%, and 1.5 g of alginic acid are dissolved in a solution obtained by mixing 75 g of 1-ethyl-3-methylimidazolium chloride and 10 ml of water, heated to 80° C., and stirred thoroughly to dissolve to obtain a cellulose solution.

[0047] 2. Preparation of spinning solution: Add 3.5 w / v% of MOFs ligand 4,4',4",4"'-methanetetrayltetrabenzoic acid to the cellulose solution prepared in step 1, stir and mix thoroughly to obtain a spinning solution.

[0048] 3. Preparation of composite nanocellulose membrane: The spinning solution obtained in step 2 was electrospun from top to bottom with a voltage of 18 kV, a receiving distance of 15 cm, a jet flow rate of 3 ml / h, and the lower half of the collecting roller was immersed in anhydrous ethanol to obtain a composite nanocellulose membrane with a membrane thickness of 80 μm.

[0049] 4. Preparation of fabrics capable of scavenging free radicals and active oxygen: The composite nanocellulose membrane obtained in step 3 was immersed in a 1.2 w / v% tetraammine copper sulfate N,N-dimethylformyl solution at a bath ratio of 40:1, and then subjected to hydrothermal reaction at a power of 500 W for 30 min, the reaction temperature was 100°C, the reaction time was 120 min, and then washed with water and dried to obtain a fabric capable of scavenging free radicals and active oxygen.

[0050] Comparative Example 1 (without chitosan and alginate)

[0051] A method for preparing a fabric comprises the following steps:

[0052] 1. Preparation of cellulose solution: Dissolve 9.6 g of absorbent cotton in 80 g of 1-allyl-3-methylimidazolium chloride and 15 ml of water, heat to 85° C., stir thoroughly to dissolve, and obtain a cellulose solution.

[0053] 2. Preparation of spinning solution: Add 4.0 w / v% of MOFs ligand 1,3,5-benzenetricarboxylic acid to the cellulose solution prepared in step 1, stir and mix thoroughly to obtain a spinning solution.

[0054] 3. Preparation of composite nanocellulose membrane: The spinning solution obtained in step 2 was electrospun from top to bottom with a voltage of 19 kV, a receiving distance of 16 cm, a jet flow rate of 4 ml / h, and the lower half of the collecting roller was immersed in anhydrous ethanol to obtain a composite nanocellulose membrane with a membrane thickness of 90 μm.

[0055] 4. Preparation of underwear fabric: The composite nanocellulose membrane obtained in step 3 was immersed in a 2.0 w / v% tetraammine copper sulfate N,N-dimethylformyl solution at a bath ratio of 45:1, and then subjected to hydrothermal reaction at 700 W power ultrasound for 25 min. The reaction temperature was 105 ° C and the reaction time was 100 min. The fabric was then washed with water and dried to obtain the fabric.

[0056] Comparative Example 2 (without MOFs ligand)

[0057] A method for preparing a fabric comprises the following steps:

[0058] 1. Preparation of spinning solution: 6.2 g of absorbent cotton, 1.7 g of chitosan with a weight average molecular weight of 400,000 and a deacetylation degree of 85%, and 1.7 g of alginic acid were dissolved in 80 g of 1-allyl-3-methylimidazole chloride and 15 ml of water, heated to 85°C, and stirred thoroughly to obtain a spinning solution.

[0059] 2. Preparation of composite nanocellulose membrane: The spinning solution obtained in step 1 was electrospun from top to bottom with a voltage of 19 kV, a receiving distance of 16 cm, a jet flow rate of 4 ml / h, and the lower half of the collecting roller was immersed in anhydrous ethanol to obtain a composite nanocellulose membrane with a membrane thickness of 90 μm.

[0060] 3. Preparation of underwear fabric: The composite nanocellulose membrane obtained in step 3 was immersed in a 2.0 w / v% tetraammine copper sulfate N,N-dimethylformyl solution at a bath ratio of 45:1, and then subjected to hydrothermal reaction at 700 W power ultrasound for 25 min. The reaction temperature was 105 ° C and the reaction time was 100 min. The fabric was then washed with water and dried to obtain the fabric.

[0061] Comparative Example 3 (Tetraammine Copper Sulfate-Free)

[0062] A method for preparing a fabric comprises the following steps:

[0063] 1. Preparation of cellulose solution: 6.2 g of cotton wool, 1.7 g of chitosan with a weight average molecular weight of 400,000 and a deacetylation degree of 85%, and 1.7 g of alginic acid were dissolved in 80 g of 1-allyl-3-methylimidazolium chloride and 15 ml of water, heated to 85° C., and stirred thoroughly to obtain a cellulose solution.

[0064] 2. Preparation of spinning solution: Add 4.0 w / v% of MOFs ligand 1,3,5-benzenetricarboxylic acid to the cellulose solution prepared in step 1, stir and mix thoroughly to obtain a spinning solution.

[0065] 3. Preparation of composite nanocellulose membrane: The spinning solution obtained in step 2 was electrospun from top to bottom with a voltage of 19 kV, a receiving distance of 16 cm, a jet flow rate of 4 ml / h, and the lower half of the collecting roller was immersed in anhydrous ethanol to obtain a composite nanocellulose membrane with a membrane thickness of 90 μm.

[0066] 4. Preparation of underwear fabric: The composite nanocellulose membrane obtained in step 3 was immersed in N, N-dimethylformyl solution at a bath ratio of 45:1, and then subjected to hydrothermal reaction at 700 W ultrasonic power for 25 min. The reaction temperature was 105 ° C and the reaction time was 100 min. Then the fabric was washed with water and dried to obtain the fabric.

[0067] Experimental Example 1: Free Radical Scavenging Experiment

[0068] The scavenging ability of 1,1-diphenyl-2-trinitrophenylhydrazine (DPPH) was used to test the scavenging ability of the fabrics of Examples 1-3 and Comparative Examples 1-3 and commercially available underwear fabrics (1. Cotton bottom crotch of AM239231 panties; 2. Embry Form small chest push-up vest bra EBW0642-246932 cup part). The results are shown in Figure 2 .

[0069] Depend on Figure 2 It can be seen that the fabric prepared in the embodiment of the present invention has excellent DPPH scavenging ability. In comparison, the DPPH scavenging ability of the comparative example and the commercial underwear fabric is poor. The reason is that the fabric of comparative example 1 does not contain chitosan and alginate during the preparation process, so it cannot form a complete composite organic metal framework structure Cu-cMOFs, and the ability to scavenge free radicals is weak. The fabric of comparative example 2 does not contain MOFs ligands, and cannot form a complete composite organic metal framework structure Cu-cMOFs. 2+ It can only coordinate with cellulose, chitosan and alginate, and has weak catalytic ability and low DPPH scavenging ability. 2+It cannot act as the central atom of the protein, cannot exhibit SOD-like and CAT-like activities, and does not have the ability to scavenge free radicals.

[0070] Experimental Example 2: Antibacterial Experiment

[0071] GBT 20944.3-2008 "Evaluation of antibacterial properties of textiles - Part 3 - Oscillation method" was used to test the antibacterial ability of the fabrics of Examples 1-3 and Comparative Examples 1-3 and commercially available underwear fabrics (1. Cotton bottom crotch of AM239231 panties; 2. Cup part of Embry Form small chest push-up vest bra EBW0642-246932) against Staphylococcus aureus, Escherichia coli and Candida albicans. The results are shown in Table 1. Figure 3 .

[0072] Depend on Figure 3 It can be seen that the fabric prepared in the embodiment of the present invention has excellent antibacterial ability. In comparison, the antibacterial ability of the underwear fabric on the market is slightly inferior, followed by the fabrics of Comparative Examples 1 and 2, and the fabric of Comparative Example 3 has the worst antibacterial ability. The reason is that in the preparation process of the fabric of Comparative Example 1, there is no chitosan and alginate, so it cannot form a complete composite organic metal framework structure Cu-cMOFs, cannot be activated by free radicals and active oxygen, and the bactericidal performance is reduced. There is no MOFs ligand in the fabric of Comparative Example 2, and it cannot form a complete composite organic metal framework structure Cu-cMOFs. 2+ It can only be connected with cellulose, chitosan and alginate by coordination bonds, and its catalytic ability is weak and its bactericidal ability is also reduced. 2+ It cannot act as the central atom of , cannot exhibit SOD-like and CAT-like activities, and will not be activated by free radicals and reactive oxygen species, so it does not have bactericidal properties.

[0073] Experimental Example 3: Active oxygen scavenging and urea decomposition experiment

[0074] The fabrics of Examples 1-3 and Comparative Examples 1-3 and commercially available underwear fabrics (1. Cotton bottom crotch of AM239231 panties; 2. Cup portion of Embry Form small chest push-up vest bra EBW0642-246932) were placed in solutions containing a certain concentration of hydrogen peroxide and urea, and the concentration changes of hydrogen peroxide and urea were detected. The clearance rate of hydrogen peroxide and the degradation rate of urea in 24 hours were calculated. The results are shown in Table 1. Figure 4 .

[0075] Depend on Figure 4It can be seen that the fabric prepared in the embodiment of the present invention has excellent hydrogen peroxide scavenging ability and urea decomposition ability. In comparison, the hydrogen peroxide scavenging ability and urea decomposition ability of the comparative example and commercially available underwear fabrics are not good. The reason is that similar to the DPPH removal experiment, the comparative example 1 fabric preparation process does not contain chitosan and alginate, and cannot form a complete composite organic metal framework structure Cu-cMOFs, so it cannot be activated by free radicals and active oxygen, and does not have the ability to oxidize and degrade urea. The comparative example 2 fabric does not have MOFs ligands, and cannot form a complete composite organic metal framework structure Cu-cMOFs. 2+ It can only be connected to cellulose, chitosan and alginate by coordination bonds, and has weak catalytic ability, hydrogen peroxide removal ability and urea decomposition ability. 2+ It cannot act as the central atom of SOD and CAT and does not have the ability to scavenge hydrogen peroxide or decompose urea.

[0076] The present invention provides a fabric that can remove free radicals and active oxygen, a preparation method thereof, and a method and idea for its application in underwear. There are many methods and approaches to implement the technical solution. The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the protection scope of the present invention. All components not specified in this embodiment can be implemented by existing technologies.

Claims

1. A method for preparing a fabric capable of removing free radicals and active oxygen, characterized in that: The steps include: S1. After the ionic liquid and water are mixed, absorbent cotton, chitosan and alginate are added to prepare a cellulose solution; S2. Adding MOFs ligands to the cellulose solution obtained in step S1, stirring and mixing thoroughly to obtain a spinning solution; S3. electrospinning the spinning solution obtained in step S2 from top to bottom to obtain a composite nanocellulose membrane; S4. Immerse the composite nanocellulose membrane obtained in step S3 in a solution of tetraammine copper sulfate in N,N-dimethylformamide, perform hydrothermal reaction after ultrasonication, wash with water, and dry to obtain a fabric that can remove free radicals and active oxygen.

2. The preparation method according to claim 1, characterized in that: The ionic liquid is one of 1-allyl-3-methylimidazolium chloride, 1-methyl-3-butylimidazolium chloride and 1-ethyl-3-methylimidazolium chloride.

3. The preparation method according to claim 1, characterized in that: In step S1, the feed ratio of the absorbent cotton, chitosan, alginic acid, ionic liquid and water is (5.8-6.5) g: (1.5-2.0) g: (1.5-2.0) g: (75-90) g: (10-20) ml.

4. The preparation method according to claim 1, characterized in that: The MOFs ligand is one of 1,3,5-benzenetricarboxylic acid, terephthalic acid and 4,4',4",4'-methanetetrayltetrabenzoic acid.

5. The preparation method according to claim 1, characterized in that: In the spinning solution, the content of MOFs ligand is 3.5-5.0 w / v%.

6. The preparation method according to claim 1, characterized in that: The lower half of the collecting roller of the electrospinning is immersed in anhydrous ethanol; the voltage of the electrospinning is 18-20 kV, the receiving distance is 15-18 cm, and the injection flow rate is 3-5 ml / h.

7. The preparation method according to claim 1, characterized in that: In step S4, the bath ratio of the immersion is 40-50:1, and the concentration of the tetraamminecopper sulfate in the N,N-dimethylformamide solution of tetraamminecopper sulfate is 1.2-3.0 w / v%.

8. The preparation method according to claim 1, characterized in that: In step S4, the hydrothermal reaction temperature is 100-110° C., and the reaction time is 60-120 min.

9. The fabric capable of scavenging free radicals and active oxygen is prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the fabric capable of scavenging free radicals and active oxygen as claimed in claim 9 in underwear.